On Site Identifications Old and New: The Example of Tell el-Hesi - Blakely, Jeffrey A. (Near Eastern archaeology, 2001)
Recent archaeological theorists of the "Interpretive School" emphasize that extracting meaning from ancient finds is a hermeneutic enterprise, a spiral of dialogue between observation and understanding, rather than a traditional scientific enterprise. The authors develop a complex argument, one that fruitfully bridges text and strata, to consider each of the host of possible identities that have been proposed for this key community in the southern Levant.